Autoimmunity and effector recognition in Arabidopsis thaliana can be uncoupled by mutations in the RRS1‐R immune receptor. Issue 2 (3rd February 2019) - Newman, Toby E.; Lee, Jungmin; Williams, Simon J.; Choi, Sera; Halane, Morgan K.; Zhou, Jun; Solomon, Peter; Kobe, Bostjan; Jones, Jonathan D. G.; Segonzac, Cécile; Sohn, Kee Hoon
Summary: Plant nucleotide‐binding leucine‐rich repeat (NLR) disease resistance proteins recognize specific pathogen effectors and activate a cellular defense program. In Arabidopsis thaliana (Arabidopsis), Resistance to Ralstonia solanacearum 1 (RRS1‐R) and Resistance to Pseudomonas syringae 4 (RPS4) function together to recognize the unrelated bacterial effectors PopP2 and AvrRps4. In the plant cell nucleus, the RRS1‐R/RPS4 complex binds to and signals the presence of AvrRps4 or PopP2. The exact mechanism underlying NLR signaling and immunity activation remains to be elucidated. Using genetic and biochemical approaches, we characterized the intragenic suppressors of sensitive to low humidity 1 ( slh1 ), a temperature‐sensitive autoimmune allele of RRS1‐R . Our analyses identified five amino acid residues that contribute to RRS1‐R SLH 1 autoactivity. We investigated the role of these residues in the RRS1‐R allele by genetic complementation, and found that C15 in the Toll/interleukin‐1 receptor (TIR) domain and L816 in the LRR domain were also important for effector recognition. Further characterization of the intragenic suppressive mutations located in the RRS1‐R TIR domain revealed differing requirements for RRS1‐R/RPS4‐dependent autoimmunity and effector‐triggered immunity. Our results provide novel information about the mechanisms which, in turn, hold an NLR protein complex inactive and allow adequate activation in the presence of pathogens.